(3eOGQc GdCMcGe aj TQM TQGFY GdESdGes - (3GdYGedj, GdehShj, GdLYHj, eMeO Hf Ydj Hf GdMSjf Hf CHj GdMSf, J (B1009s ((3eMeO QajY Hf edG eMeO bGSe GdQTJj GdchSajgGfjs)
(3ChdgG (B:s
(3GdMeO ddg cKjQG ceG gh Cgdg (B... (3GdaUd GdKGdK aj UdGI GdcSha hGdcdGe hSHHgG hcjajJgG hMcegG bGd aj GdbGehS jbGd cSa GdTeS hGdbeQ cShaG GMJLGHG cGfcSa (B...s
(3BNQgG (B:s
... (3eJYdbG HCSJGQ GdcYdHI hgh jbhd Gddge GfJbe dj ef ??? eG QhGg GHf HGHhjg aj GdUMjM CjVG Yf HcjQ Hf CYjf Yf CNjg Yf RQGQI bGd bdJ dCHj (B... (3hGdMeO ddg ChdG hBNQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B20/2765s
(3GdPQjYI (B20/2765s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis